KNAT7 regulates xylan biosynthesis in Arabidopsis seed-coat mucilage. (11th April 2020) - Wang, Yiping; Xu, Yan; Pei, Shengqiang; Lu, Mingmin; Kong, Yingzhen; Zhou, Gongke; Hu, Ruibo
Abstract : KNAT7 acts as a transcriptional activator of xylan biosynthesis in Arabidopsis seed mucilage by directly activating the expression of IRX14 and MUM5 . Abstract: As a major hemicellulose component of plant cell walls, xylans play a determining role in maintaining the wall structure. However, the mechanisms of transcriptional regulation of xylan biosynthesis remain largely unknown. Arabidopsis seed mucilage represents an ideal system for studying polysaccharide biosynthesis and modifications of plant cell walls. Here, we identify KNOTTED ARABIDOPSIS THALIANA 7 (KNAT7) as a positive transcriptional regulator of xylan biosynthesis in seed mucilage. The xylan content was significantly reduced in the mucilage of the knat7-3 mutant and this was accompanied by significantly reduced expression of the xylan biosynthesis-related genes IRREGULAR XYLEM 14 ( IRX14 ) and MUCILAGE MODIFIED 5 / MUCILAGE-RELATED 21 ( MUM5 / MUCI21 ). Electrophoretic mobility shift assays, yeast one-hybrid assays, and chromatin immunoprecipitation with quantitative PCR verified the direct binding of KNAT7 to the KNOTTED1 (KN1) binding site [KBS, TGACAG(G/C)T] in the promoters of IRX7, IRX14, and MUM5 / MUCI21 in vitro, in vivo, and in planta . Furthermore, KNAT7 directly activated the expression of IRX14 and MUM5/MUCI21 in transactivation assays in mesophyll protoplasts, and overexpression of IRX14 or MUM5 / MUCI21 in knat7-3 partially rescued the defects in mucilage adherence. Taken together, our results indicate that KNAT7 positively regulates xylan biosynthesis in seed-coat mucilage via direct activation of the expression of IRX14 and MUM5 / MUCI21 .